PROFIL MUTU KOMODITI UNGGULAN PERKEBUNAN KABUPATEN ENDE (KOMODITI KEMIRI) - Emilia S.A. Wangge (Agriculture Faculty of Flores University, 2014)
The study of the quality profile of plantation excellent commodity in Ende Regency (hazelnut commodity) is to provide information about the degree composition of water and fat on hazelnut commodity in Ende Regency. Hazelnut commodity profile benefits for the provision of trade opportunity information and the investment of hazelnut cultivation to both foreign and domestic investors, as well as business persons, in order to boost the investment growth in Ende Regency. This study was conducted in the Agriculture Technology Laboratory of the Udayana University of Denpasar. The presentation of hazelnut commodity profile in Ende Regency of East Nusa Tenggara Province apparently reveals that this region has great potential to be further developed viewed from the quality content aspect.